Idiopathic recurrent facial palsy: a detailed investigation - Kandasamy, Sasirekah; Jayakumar, Priya; Balasubramanian, Ganesan; Saburdeen, Thameem Ansari; Balasubramaniam, Arun; Murugaiyan, Poovarasan; Umasankar, Yamini; Srinivasan, Vignesh; Suganthirababu, Prathap (International Journal of Research in Medical Sciences, 2026)
The seventh cranial nerve may be partially or completely damaged, resulting in central or peripheral facial palsy. This leads to weakness of facial muscles, distorted facial expressions and drooling on the affected side. Common causes include cold exposure, pregnancy-related fluid retention, middle ear infections and herpes zoster infection. This case report discusses a 33-year-old male, Mr. RSY, who presented with right-sided facial palsy for the fifth time. Previous episodes occurred annually from 2020 to 2023. He is a chef from Erode who presented to the Medicine OPD with mouth deviation, incomplete right eye closure with positive Bell’s phenomenon, and mild headache and neck pain. He had no relevant medical history or recent cold exposure. Blood tests were normal and chest X-ray revealed mild hilar lymphadenopathy. ENT examination and HRCT of the temporal bone were normal. The only notable finding was the involvement of the seventh cranial nerve. Management included a seven-day course of corticosteroids, antiviral drugs and physiotherapy. The physiotherapy regimen comprised facial massage, facial exercises and stimulation. A home exercise program was also advised. The patient improved significantly with this combined treatment and recovered within four weeks. This case underscores the importance of early and comprehensive management of facial palsy with corticosteroids and physiotherapy for full recovery. It also highlights some patients’ potential seasonal recurrence patterns, warranting further research to elucidate the exact pathogenesis and risk factors associated with facial palsy.